2020
DOI: 10.1094/mpmi-03-20-0062-r
|View full text |Cite
|
Sign up to set email alerts
|

The Mitogen-Activated Protein Kinase Gene Crmapk Is Involved in Clonostachys chloroleuca Mycoparasitism

Abstract: Clonostachys chloroleuca is a mycoparasite used for biocontrol of numerous fungal plant pathogens. Sequencing of the transcriptome of C. chloroleuca following mycoparasitization of the sclerotia of Sclerotinia sclerotiorum revealed significant upregulation of a mitogen-activated protein kinase (MAPK)-encoding gene, crmapk. Although MAPKs are known to regulate fungal growth and development, the function of crmapk in C. chloroleuca mycoparasitism is unclear. In this study, we investigated the role of crmapk in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…To investigate mycoparasitism-related genes in C. chloroleuca , the transcriptome of the strain 67-1 associated with S. sclerotiorum sclerotia was sequenced and the differentially expressed genes 8 h, 24 h and 48 h after sclerotia induction were analysed 9 . Combining with these results, we found that 38 interacting genes were differentially expressed (|Log 2 FC| ≥ 1 and p ≤ 0.05; Table 1 ), among which 15 genes ( NODE_15_2 , NODE_171_30 , NODE_176_9 , NODE_198_20 , NODE_2_38 , NODE_201_16 , NODE_374_8 , NODE_38_86 , NODE_486_20 , NODE_507_12 , NODE_52_12 , NODE_525_9 , NODE_558_28 , NODE_606_27 and NODE_98_38 ) were upregulated by at least 1.2-fold at 8 h, similar to expression of Crmapk that especially highly expressed at 8 h during the mycoparasitic process of C. chloroleuca 67-1 10 . To explore the roles and mechanisms of Crmapk in C. chloroleuca mycoparasitism, the gene was deleted using gene homologous recombination strategy, and the transcriptome analysis of ΔCrmapk mutant mycoparasitising S. sclerotiorum sclerotia was performed before 10 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate mycoparasitism-related genes in C. chloroleuca , the transcriptome of the strain 67-1 associated with S. sclerotiorum sclerotia was sequenced and the differentially expressed genes 8 h, 24 h and 48 h after sclerotia induction were analysed 9 . Combining with these results, we found that 38 interacting genes were differentially expressed (|Log 2 FC| ≥ 1 and p ≤ 0.05; Table 1 ), among which 15 genes ( NODE_15_2 , NODE_171_30 , NODE_176_9 , NODE_198_20 , NODE_2_38 , NODE_201_16 , NODE_374_8 , NODE_38_86 , NODE_486_20 , NODE_507_12 , NODE_52_12 , NODE_525_9 , NODE_558_28 , NODE_606_27 and NODE_98_38 ) were upregulated by at least 1.2-fold at 8 h, similar to expression of Crmapk that especially highly expressed at 8 h during the mycoparasitic process of C. chloroleuca 67-1 10 . To explore the roles and mechanisms of Crmapk in C. chloroleuca mycoparasitism, the gene was deleted using gene homologous recombination strategy, and the transcriptome analysis of ΔCrmapk mutant mycoparasitising S. sclerotiorum sclerotia was performed before 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Combining with these results, we found that 38 interacting genes were differentially expressed (|Log 2 FC| ≥ 1 and p ≤ 0.05; Table 1 ), among which 15 genes ( NODE_15_2 , NODE_171_30 , NODE_176_9 , NODE_198_20 , NODE_2_38 , NODE_201_16 , NODE_374_8 , NODE_38_86 , NODE_486_20 , NODE_507_12 , NODE_52_12 , NODE_525_9 , NODE_558_28 , NODE_606_27 and NODE_98_38 ) were upregulated by at least 1.2-fold at 8 h, similar to expression of Crmapk that especially highly expressed at 8 h during the mycoparasitic process of C. chloroleuca 67-1 10 . To explore the roles and mechanisms of Crmapk in C. chloroleuca mycoparasitism, the gene was deleted using gene homologous recombination strategy, and the transcriptome analysis of ΔCrmapk mutant mycoparasitising S. sclerotiorum sclerotia was performed before 10 . In this study, it showed that when Crmapk was deficient 11 putative interacting genes from the Y2H library were differentially expressed (|Log 2 FC| ≥ 1 and p ≤ 0.05) based on the transcriptome profile of the C. chloroleuca mutant mycoparasitising sclerotia (Table 2 ), indicating that these genes might be involved in similar pathways to Crmapk .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In F. graminearum, the phosphorylation of Mgv1 was inhibited by HopAI, an effector from Pseudomonas syringae (Zhang et al, 2017). Similar to their plant and animal counterparts, filamentous fungi have Nod-like immune receptors (NLRs) for signal recognition and activation of downstream targets (Uehling et al, 2017). F. graminearum has over 60 predicted NLR genes and some of them may be involved in recognizing MAMPS and fungal-bacterial interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Several mycoparasitism-related differentially expressed genes (DEGs) have been reported. Signal transduction or signaling-related proteins, including G-proteins and mitogen-activated protein kinases (MAPKs), are involved in a series of processes, e.g., recognition or sensing the host or prey, (interspecific) communication, and attachment of parasitic appressorium-like structure(s) to the host (Omero et al 1999 ; Reithner et al 2007 ; Sun et al 2020 ; Yang 2017 ; Zeilinger et al 2005 ). In the S. mycoparasitica transcriptome, the expression levels of transcripts encoding G-proteins and MAPKs were higher during the interaction with the host than in controls (without host interactions) (data are not shown).…”
Section: Discussionmentioning
confidence: 99%